GOLDEN ALGAE (CHRYSOPHYTA) BIODIVERSITY OF THE MOUNTAINOUS CRIMEA AND UKRAINIAN CARPATHIANS - Nykyforov, V.V. (World of Medicine and Biology, 2021)
As a result of algological studies of different types of water bodies in the Crimean Mountains and the Ukrainian Carpathians, 144 Chrysophyta species were identified, represented by 154 taxa of intraspecies rank, including the nomenclature type of the species. For the first time, 82 (90) species are indicated for the golden algae flora of Ukraine, including three species described as new to science: Dinobryon emoriens, Kephyrion perforatum, Mallomonas montana. Ecological and geographical features, species composition, abundance and systematic structure of chrysophytes were established, as well as their uneven distribution in water bodies, which manifests itself in a decrease in species diversity in the following sequence: swamps → lakes → ponds → rivers.